Strategic Integration of Corporate Social Responsibility into Governance and Business Models of Philippine Private Higher Education Institutions - Hazel S. Osano; Anik Yuesti; Joel Arante Alve (EMAS: Jurnal Ekonomi, Manajemen dan Bisnis, 2026)
Philippine private higher education institutions (HEIs) operate in a constrained environment where the delivery of a public-good service is closely tied to tuition dependence, enrollment uncertainty, and cost pressures that are difficult to pass on to families. In this context, this study examined how corporate social responsibility (CSR) was integrated into the governance and operating practices of private HEIs facing financial and competitive pressure. Using a multiple- case, mixed-method design, the research analyzed how CSR priorities were embedded in board oversight, budgeting, monitoring routines, student support systems, and institutional reporting. The findings showed that while most institutions articulated CSR commitments clearly, meaningful differences emerged in governance discipline rather than in values language. CSR initiatives were more stable in HEIs where responsibilities were supported by formal policies, protected budget lines, and routine review processes, particularly under tuition dependence and enrollment volatility. The study also found uneven credibility in CSR reporting, with recruitment pressures sometimes blurring reporting and promotion. Institutions with clearer indicators, assigned data ownership, and basic review controls produced more credible disclosures, even when reporting fewer items. Stakeholder trust was most strongly associated with education- specific responsibilities directly experienced by students and staff, including scholarship transparency, student welfare systems, fair academic procedures, and accessible learning support.